Innovation of learning methods during the covid-19 pandemic at junior high school in Mataram City and West Lombok Regency - Fidiani Fidiantara; Ayudya Lestari; Norma Juniati; Abdul Syukur; Jamaluddin Jamaluddin (Jurnal Pijar Mipa, 2021)
Learning innovation is a solution to achieve learning mastery, especially during the covid-19 pandemic. This study aims to describe and assess models of learning innovation methods that are relevant to changes in learning models during the covid-19 pandemic. The method used in this research is descriptive method and the sampling technique is simple random sampling. Meanwhile, the data collection techniques used documentation studies and interviews. Data analysis in this study was descriptive statistics andtest one-way anova using software spssversion 17.0. The results showed that: 1) the innovation of learning methods during the covid-19 pandemic with blended learning showed a sig.> 0.05 value, namely 0.428 at junior high school mataram city and 0.442 at junior high school West Lombok Regency , which means there is no significant difference in the implementation of the learning method. Blended learning during the covid-19 pandemic; 2) teacher perceptions based on 5 indicators, namely learning methods, innovation in the learning process, use of technology, lesson planning, and teacher support capacity indicate that science teachers at junior high school mataram city and west lombok regency have perceptions of 87.5% and 75.0% with good category; 3) students' perceptions based on 5 indicators, namely the effectiveness of the methods used, the use of technology, learning activities, learning motivation, and the carrying capacity of facilities and infrastructure indicate that students at junior high school mataram city have a perception of 90% with a good category and west lombok regency of 72.5% with good enough category. The conclusion of this study is that learning innovation or a combination of methods through online learning methods with blended learning during the covid-19 pandemic is a solution to achieve student learning mastery.